Prevalence of Methicillin-Resistant Staphylococcus aureus among Intensive Care Unit Healthcare Workers: A Single Center Study - Maelanti Norma; Fathiyah Isbaniah; Bagus Radityo Amien; Fathia Amalia Faizal; Syafira Radhwadanti (Jurnal Respirasi, 2026)
Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of nosocomial infections, contributing to increased mortality, morbidity, and healthcare costs. Healthcare workers (HCWs) in intensive care units (ICUs) are at increased risk of MRSA colonization and may serve as vectors for transmission. Therefore, screening for MRSA carriage is essential for the prevention and control of MRSA infections. This study aimed to determine the prevalence of MRSA colonization and identify associated factors among ICU HCWs. Methods:  A cross-sectional study was conducted at Persahabatan National Respiratory Referral Hospital, Jakarta, Indonesia, in June 2023. The MRSA detection was performed by polymerase chain reaction (PCR) using Xpert® MRSA NxG, with samples collected from nasal swabs. Bivariate analysis was performed to assess risk factors associated with MRSA colonization. Results: Of the 150 participants, 4% of HCWs were colonized with MRSA. Nurses (4.2%) showed a higher prevalence than doctors (3.1%). A higher prevalence of MRSA colonization was also observed in one of the ICU units (ICU Madya), with 4 out of 22 respondents (18.2%) testing positive. No risk factors were significantly associated with MRSA colonization (p>0.05), but males showed a relatively high odds ratio/OR (p=0.182, OR 3). Conclusion: A low prevalence of MRSA colonization was observed among all ICU HCWs. However, a higher prevalence was noted among staff in one of the ICU units. No significant associations were identified between potential risk factors and MRSA colonization.  Nurses and male HCWs demonstrated a higher risk of MRSA colonization.